Experimental study on the mechanical behavior of RPC filled square steel tube columns subjected to eccentric compression - Wenxiu Hao; Xiao Xu; Zhiqiang Niu (Fracture and Structural Integrity)
In order to study the mechanical behavior of reactive powder concrete (RPC) filled square steel tubular columns, this paper designs an eccentric compression experiment for 12 specimens of RPC filled square steel tubular columns and studies the effects of failure form, load-displacement curve, slenderness ratio, steel ratio and eccentricity ratio of an eccentrically loaded columns on its mechanical behavior. At the same time, it also compares the experiment results with the bearing capacity calculated with relevant specifications and uses Abaqus to carry out numerical simulation of eccentrically loaded columns. The results show that, the failure form of the eccentrically loaded RPC filled square steel tubular column shows local buckling failure. Before the ultimate load is reached, there is no significant change on the surface of the specimen, and the yield stage of the load-displacement curve is not obvious, either. The results of the bearing capacity calculation formula recommended in CECS28-2012 are close to the experiment results and relatively conservative, so it is more applicable to the bearing capacity design of eccentrically loaded RPC filled square steel tubular columns. The results of the numerical simulation analysis are in good agreement with the experimental results, which can provide theoretical support for engineering practice.